Diagnosa Penyakit Hepatitis Menggunakan Metode Weighted Product - Sihaloho, Parlindungan; Ginting, Wasit (LPPM UNIKA Santo Thomas Medan, 2017)
Hepatitis is an inflammatory process in the liver tissue. Hepatitis in lay language is often referred to as liver or jaundice. Viral hepatitis infection can develop into cirrhosis or hardening of the liver even liver cancer, inflammation / inflammation and injury to the liver due to hepatic reactions to various conditions, especially viruses, drugs and alcohol. Hepatitis Diagnosis Expert System has been developed with a weighted product method. The weight product method diverts the results of the assessment of each attribute. The results of these multiplications have not been meaningful if they have not been compared with standard values. The weight for the benefit attribute functions as a positive power in the multiplication process, while the cost weight functions as a negative power multiplying the attribute value of each symptom that has been weighted for.From the results of the trials that have been carried out the system has been able to diagnose hepatitis A, B, C, D, E based on the symptoms entered by the patient.